(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Drug is an essential tool of a physician included in Chatushpada. Many single as well as compound drugs are mentioned in classics in different contexts for internal as well as external use. It is always the cumulative impact of all the ingredients in the solution that plays a critical role in therapeutics, rather than the action of the individual medication. Synergistic action, combined action and toxicity neutralizing action and basic purpose are envisaged to serve drug combinations. One such important formulation prescribed in the Ashtanga Haridya Uttartantra is Gokshuradi Churna provides specifics of the drugs Gokshuradi Churna which was chosen for study. Acharya Vaghbhatta in Uttartantra listed numerous drugs that are useful in the treatment of Alpa, Dushta Retas that specifically influence the properties of Shukrajanana (spermatogenesis) and Shukra Shodhana. This formulation consists of five ingredients i.e., Gokshura (Tribulus terrestris Linn), Ikshura (Asteracantha longifolia Nees), Mash (Phaseolus mungo Linn), Atmagupta seeds (Mucuna prurita Hook) & Shatavari (Asparagus racemosus Wild). Many formulations are available in various texts under the same name Gokshuradi Churna with different ingredients and different Rogadhikara. Keeping this aim into consideration, the present study was designed to scientific evaluation of Gokshuradi Churna and its hydroalcoholic extract on different analytical and phytochemical parameters. The study includes macro and microscopic characters, powder microscopic characteristics, heavy metals analysis and High Performance Thin Layer Chromatography fingerprints (HPTLC). The information generated by this particulars study provides relevant pharmacognostical and physicochemical data needed for proper identification and authentication of Gokshuradi Churna and its hydroalacoholic extract.